Mapping the landscape of brain stimulation research: A global scientometric review on cognitive impairment - Mani Abdul Karim (Ibrain)
Abstract Several noninvasive brain stimulation techniques have gained significant attention in neurocognitive science and clinical research due to their potential efficacy in addressing neurological, psychiatric, and cognitive impairments. This study explores global trends and research hotspots in brain stimulation research for cognitive impairment and related disorders. Using a data set from 1989 to 2024 sourced from the Web of Science Core Collection, 4156 records were analyzed through bibliometric methods, including publication trends, country or region, and institutional analysis, and document co‐citation analysis (DCA). Results revealed a steady increase in research, with a significant increase in publications during the period from 2019 to 2023. The USA led in citation counts (1117), centrality (0.37), while China topped the burst value (72.31). The University of London led in citation counts (235), whereas Capital Medical University topped the sigma value (1.77). Transcranial magnetic stimulation (TMS) and repetitive TMS (rTMS) dominated the top positions in DCA analysis. Emerging trends were identified through burst keywords, including “transcranial Doppler,” “subthalamic nucleus stimulation,” “cerebral blood flow,” “vascular dementia,” and “cardiopulmonary bypass.” These emerging research hotspots underscore the growing focus on vascular aspects of cognitive impairment and advanced brain stimulation methods. Additionally, newer noninvasive techniques like fast gamma magnetic stimulation, paired‐associative stimulation with TMS (PAS‐TMS), and theta‐burst stimulation are identified as promising avenues for future research, offering significant potential for therapeutic advancements. This study provides a comprehensive overview of the global landscape, trends, and future directions in brain stimulation research for cognitive impairment.